Vocal fold leukoplakia: Diagnostic approaches, risk stratification, and management of laryngeal premalignant lesions - Farhat, Muhammad Fauzi (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2026)
Background: Vocal cord leukoplakia is a diverse epithelial condition with indeterminate biological characteristics, resulting in ongoing conflict between early oncological intervention and voice preservation. To integrate current knowledge about diagnostic methodologies, risk classification, and the management of vocal cord leukoplakia and associated laryngeal precancerous lesions. Method: This narrative literature review focused on English-language journal papers published from 2016 to April 2026, with the final selection restricted to studies published in Scopus-indexed publications. Primary cohort studies, diagnostic investigations, systematic reviews, meta-analyses, and a 2021 position document from the European Laryngological Society were given top priority. Results: The most consistent message from recent research is that combining white-light laryngoscopy with stroboscopy, narrowband imaging, and histopathology makes diagnosis more accurate. Lesions that are rough, thick, hyperemic, and non-vibrating and have an unusual vascular pattern are more likely to lead to severe dysplasia or cancer. Histologic grade, on the other hand, is still the most important factor in determining whether a tumor will turn malignant over time. Conservative treatment seems best for certain modest lesions. On the other hand, suspicious, persistent, recurrent, or histologically progressed lesions usually need a biopsy or excision. Conclusion: Contemporary management options for vocal cord leukoplakia must be multimodal, risk-adapted, and explicitly associated with longitudinal surveillance. Future research should concentrate on standardized scoring systems, external validation of optical biopsy instruments, and biomarker-driven predictive models.